The Analysis of Code Mixing Used on Livy Renata's Vlog - I Gusti Ayu Venisa Ramayani Venisa Ramayani; Anak Agung Istri Manik Warmadewi (Center of Language and Cultural Studies, 2023)
The objective of this research is to: 1) analyze the type of code mixing used on Livy Renata’s Vlog on YouTube channel, 2) analyze the factors caused code mixing uses Livy Renata’s Vlog. This research applied Muysken's code mixing theory as well as JU's code mixing factors. Descriptive qualitative employed in this research. The data of this research consists of Livy’s phrase on her vlog that contain a code mixing. There were 56 code mixingfound in this research. The categorization of the data analysis's findings was used to insertion, alternation, and congruent lexicalization. The findings revealed that the most typical style of code mixing was insertion (67,8%), it was followed by alternation (17,85%), and congruent lexicalization (14,28%). There are four factors of caused use code mixing in this research they are language dominance, language attitude, psycholinguistics motivation, and mixing in highly accessible word or phrase.